Greater endothelial activation, Weibel-Palade body release and host inflammatory response to Plasmodium vivax, compared with Plasmodium falciparum: a prospective study in Papua, Indonesia. - Yeo, T; Lampah, D; Tjitra, E; Piera, K; Gitawati, R; Kenangalem, E; Price, R; Anstey, N (2010)
Pathogenic mechanisms underlying vivax malaria are poorly understood, with few studies comparing endothelial and inflammatory responses with falciparum malaria. In adults with uncomplicated vivax or falciparum malaria, we compared plasma measurements of endothelial Weibel-Palade body release (angiopoietin-2) and activation (ICAM-1, E-selectin), as well as selected cytokines. Despite a lower median parasite count, angiopoietin-2 concentrations were higher in patients with vivax malaria, compared with falciparum malaria. Per peripheral parasite, median plasma angiopoietin-2, ICAM-1, E-selectin, interleukin-6, and interleukin-10 concentrations were higher in patients with malaria due to Plasmodium vivax. P. vivax induces greater endothelial Weibel-Palade body release and activation and greater host inflammatory responses, compared with Plasmodium falciparum.